Contractile Protein Expression and Phosphorylation and Contractility of Gastric Smooth Muscles from Obese Patients and Patients with Obesity and Diabetes - Wen Li; Kent C. Sasse; Yulia Bayguinov; Sean M. Ward; Brian A. Perrino (Journal of Diabetes Research)
Ingested food is received, mixed, and ground into chyme by distinct gastric motility patterns. Diabetes impairs gastric muscle function, but the mechanisms underlying diabetes-induced gastric muscle dysfunction are unknown. Here, we compared the expression and phosphorylation of Ca2+ sensitization and contractile proteins in human gastric muscles from obese nondiabetic and diabetic patients. We also compared the spontaneous phasic contractions and the contractile responses evoked by electrical field stimulation of cholinergic motor neurons. Fundus and antrum muscles were obtained from sleeve gastrectomies and were used in in vitro myobath contractile studies and for capillary electrophoresis and immunodetection of γ-actin, CPI-17, pT38-CPI-17, MYPT1, pT853-MYPT1, pT696-MYPT1, myosin light chain (MYL9), pS19-MYL9, myosin light chain kinase (MYLK), protein phosphatase-1δ (PP1δ), and Rho-associated kinase (ROCK2). In diabetic fundus muscles, MYLK, ROCK2, and PP1δ expression was unchanged; MYPT1 and CPI-17 expression was decreased; and the pT853/MYPT1 and pT38/CPI-17 ratios, but not the pT696/MYPT1 ratio, were increased. Although MYL9 expression was increased, the pS19/MYL9 ratio was unchanged in diabetic fundus muscles. In diabetic antrum muscles, MYLK and MYL9 expression was unchanged, but ROCK2, CPI-17, and PP1δ expression was decreased. The pT38/CPI-17 ratio was unchanged, while the pS19/MYL9, pT853/MYPT1, and pT696/MYPT1 ratios were decreased, consistent with the reduced ROCK2 expression. The frequencies of spontaneous phasic contractions from nondiabetic and diabetic gastric fundus and antrum muscles did not significantly differ from each other, regardless of age, sex, or diabetic status. The fold increases in the contractions of diabetic fundus and antrum muscles in response to increased frequencies of electrical field stimulation were significantly lower compared to nondiabetic fundus and antrum muscles. The altered contractile responses and the protein expression and phosphorylation in gastric muscles of obese patients with diabetes illustrate the importance of understanding how smooth muscle Ca2+ sensitization mechanisms contribute to gastric motility.